Sensitization rates to common inhaled allergens in Germany – increase and change patterns over the last 20 years. (26th October 2020) - Beutner, Caroline; Werchan, Barbora; Forkel, Susann; Gupta, Sidhi; Fuchs, Thomas; Schön, Michael P.; Geier, Johannes; Buhl, Timo
Summary: Background: Sensitization rates to aeroallergens are rising worldwide. The prevalence is increasing, especially in Western countries. We aimed to investigate (1) sensitization rates and (2) cross‐sensitization patterns in skin prick tests (SPTs) for the most relevant inhaled allergens in central Germany over 20 years, adjusted for regional pollen counts. Patients and Methods: This monocentric study evaluated SPTs for tree pollen, grass pollen and house dust mites (HDMs) in 4, 315 patients (including children) with suspected airway allergies, from 1998–2017. Results: Sensitization rates to almost all aeroallergens have increased significantly over time, without relevant changes in regional pollen counts. Current sensitization rates in all our symptomatic patients were highest for grass (55.3 %) and rye pollen (59.6 %), with most pronounced increases in HDM sensitization over time (from 37.8 % to the current figure of 50.1 %). However, a low but consistent proportion of tree‐sensitized patients (3.6–7.8 %) showed isolated positive SPTs to alder and/or hazel pollen without sensitization to birch pollen. Conclusions: We demonstrate a significant rise in the total number of sensitized patients as well as increases in cross‐sensitization between closely related allergens. Individuals with unusual mono‐sensitization profiles to common inhaled allergens should be studied in more detail, since these patients are currently excluded from clinical trials for allergen immunotherapy.